ANALISIS STRATEGI PEMASARAN COFFEE SHOP DALAM MEMENUHI GAYA HIDUP MAHASISWA GEN Z (STUDI KASUS PADA MAHASISWA UNIVERSITAS SINGAPERBANGSA KARAWANG) - Agustiyanti, Azril Akbar; Sudrajat, Ajat (Relawan Jurnal Indonesia, 2025)
This study aims to analyze the effect of coffee shop marketing strategies on the lifestyle of Generation Z students at Singaperbangsa University Karawang. Using a descriptive quantitative method and involving 100 respondents, data was collected through a questionnaire that had been tested for validity and reliability. The results of simple linear regression analysis show that marketing strategies have a positive and significant effect on student lifestyles, with a t-value of 8.377 > t-table 1.661 and significance of 0.000 < 0.05. The coefficient of determination of 41.7% indicates that marketing strategies contribute to the formation of Generation Z students' lifestyles. Thus, the implementation of effective marketing strategies through the 7P marketing mix can influence the lifestyles of Generation Z students.